mTOR Inhibitors Induce Erythropoietin Resistance in Renal Transplant Recipients - Jefferies, Reece; Puttagunta, Harish; Krishnan, Anoushka; Irish, Ashley; Swaminathan, Ramyasuda; Olynyk, John K. (Frontiers in Medicine, 2022)
Aim To elucidate the role of mTOR inhibitors on iron, hepcidin and erythropoietin-mediated regulation of hemopoiesis in stable renal transplant recipients (RTR). Background Impaired hemopoiesis is common following renal transplantation managed using mTOR inhibitors. The mechanisms responsible are uncertain but include direct effects on iron, hepcidin or erythropoietin-mediated hemopoiesis. Methods We conducted a single centre prospective case-control study of 26 adult RTR with stable allograft function. RTR received stable mTOR dosing (cases, 11/26[42%]) or stable tacrolimus dosing (controls, 15/26[58%]). Baseline demographics, full blood count, renal function, iron studies, hepcidin-25, Interleukin-6 (IL-6) and erythropoietin (EPO) levels were determined. Results There were no differences in age, gender or allograft function. Mean daily sirolimus dose for cases was 1.72mg, with mean trough level of 8.46ng/mL. Mean daily tacrolimus dose for controls was 4.3mg, with mean trough level of 5.8ng/mL. There were no differences in mean hemoglobin (143 vs 147 g/L; p=0.59), MCV (88 vs 90 fL; p=0.35), serum ferritin (150 vs 85.7 g/L; p=0.06), transferrin saturation (26 vs 23.3%;p=0.46), IL-6 (11 vs 7.02 pg/ml; p=0.14) or hepcidin-25 (3.62 vs 3.26 nM; p=0.76) between the groups. EPO levels were significantly higher in the group receiving mTOR therapy (16.8 vs 8.49 IU/L; p=.028). On logistic regression analysis EPO level was the only variable that had a significant impact providing an odds ratio of 0.84 (95%CI 0.66-0.98). The area under the receiver operator characteristic curve (ROC) for the analysis was 0.77 (95%CI 0.54-0.94) with p=0.04. Conclusion Higher levels of EPO in the absence of deranged iron biochemistry or hepcidin-25 levels suggest that EPO resistance rather than impaired iron metabolism may contribute to the impaired hemopoiesis previously demonstrated in RTR on mTOR therapy.